Role of gender in perceived stress and adjustment among adolescents in Malaysia - Yaacob, Siti Nor; Tan, Soon Aun; Esmaeili, Nooshin Sabour; Tan, Jo Pei; Juhari, Rumaya (Iceland Glaciological Society, 2013)
Background: Stress is a highly unpleasant state of emotional arousal that may relates to adjustment problems such as depression, anxiety, aggression and performance in school. This study aimed to determine the role of gender in the relationship between perceived stress and adjustment among adolescents in metropolitan and urbanized cities of Malaysia. Methods: A total of 441 school-going adolescents aged between 13 and 17 years from 15 secondary schools were selected as respondents of the study by using multistage cluster sampling method with Probability Proportional to Size (PPS) sampling technique. Results: Findings of the study indicated that adolescents with low level of stress of home life, low level of stress of peer pressure and school/leisure conflict had significantly better emotional and school functioning. T-test analysis revealed significant difference in emotional functioning between male and female respondents. Multivariate analyses revealed that gender moderated the relationship between stress experiences and adjustment. Conclusion: In conclusion, stress has a negative influence on adolescents’ adjustment. Female adolescents are more affected by stress than males.